2017
DOI: 10.1093/nar/gkx406
|View full text |Cite
|
Sign up to set email alerts
|

Cmr is a redox-responsive regulator of DosR that contributes to M. tuberculosis virulence

Abstract: Mycobacterium tuberculosis (MTb) is the causative agent of pulmonary tuberculosis (TB). MTb colonizes the human lung, often entering a non-replicating state before progressing to life-threatening active infections. Transcriptional reprogramming is essential for TB pathogenesis. In vitro, Cmr (a member of the CRP/FNR super-family of transcription regulators) bound at a single DNA site to act as a dual regulator of cmr transcription and an activator of the divergent rv1676 gene. Transcriptional profiling and DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Post-translational modifications are common mechanisms for the regulation of DNA binding both in eukaryotes (Bannister and Kouzarides, 2011) and prokaryotes (Dilweg and Dame, 2018). Phosphorylation or nitrosylation of transcriptional regulators abolish DNA binding (Leiba et al, 2014;Smith et al, 2017). H-NS protein, a homologue of Lsr2 in E. coli, has been shown to be acetylated and phosphorylated; however, the precise function of these modifications remains to be characterised (Dilweg and Dame, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications are common mechanisms for the regulation of DNA binding both in eukaryotes (Bannister and Kouzarides, 2011) and prokaryotes (Dilweg and Dame, 2018). Phosphorylation or nitrosylation of transcriptional regulators abolish DNA binding (Leiba et al, 2014;Smith et al, 2017). H-NS protein, a homologue of Lsr2 in E. coli, has been shown to be acetylated and phosphorylated; however, the precise function of these modifications remains to be characterised (Dilweg and Dame, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The functional impact of post-translational modification (PTM) of AbmR by phosphorylation is unknown, but PTM of AbmR may feed into an ATP sensing and signaling network. PknH has a demonstrated role in phosphorylating the dormancy survival response regulator (DosR) (Chao et al, 2010), and regulatory overlaps between DosR and Cmr have recently been revealed (Ranganathan et al, 2016;Smith et al, 2017). Decrypting the regulatory overlap of AbmR and cAMP responsive TFs such as CRP Mt and Cmr during infection and persistence will contribute to our understanding of Mtb's adaptation to the host environment.…”
Section: Gene Regulatory Functions Of Abmr and Regulatory Networkmentioning
confidence: 99%
“…The unique fold of Cmr also indicates a more distant evolutionary relationship with CRP/FNR TFs, as suggested previously by a phylogenetic study ( 6 ). This functional complexity may provide Cmr with the flexibility to simultaneously integrate multiple signals and modulate its DNA interactions in response to different inputs, including interactions with other TFs, such as those reported for DosR ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRP Mt is the closest Mtb ortholog of CRP Ec and is better studied than Cmr ( 19 23 ). Both Cmr and CRP Mt exhibit widespread genomic binding associated with the control of large putative regulons ( 24 26 ), and deletion of either gene attenuates Mtb virulence in a murine model ( 21 , 27 ). CRP Mt regulates serine metabolism and is required for wild-type (WT) levels of growth in liquid culture and within macrophages ( 20 , 21 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation